Ultrathin Metal–Organic Framework Nanosheets with Ultrahigh Loading of Single Pt Atoms for Efficient Visible‐Light‐Driven Photocatalytic H2 Evolution. (24th June 2019) - Zuo, Quan; Liu, Tingting; Chen, Chuanshuang; Ji, Yi; Gong, Xueqing; Mai, Yiyong; Zhou, Yongfeng
Abstract: A surfactant‐stabilized coordination strategy is used to make two‐dimensional (2D) single‐atom catalysts (SACs) with an ultrahigh Pt loading of 12.0 wt %, by assembly of pre‐formed single Pt atom coordinated porphyrin precursors into free‐standing metal–organic framework (MOF) nanosheets with an ultrathin thickness of 2.4±0.9 nm. This is the first example of 2D MOF‐based SACs. Remarkably, the 2D SACs exhibit a record‐high photocatalytic H2 evolution rate of 11 320 μmol g −1 h −1 via water splitting under visible light irradiation ( λ >420 nm) compared with those of reported MOF‐based photocatalysts. Moreover, the MOF nanosheets can be readily drop‐casted onto solid substrates, forming thin films while still retaining their photocatalytic activity, which is highly desirable for practical solar H2 production. Abstract : Ultradünne MOF‐Nanoblätter auf Porphyrinbasis mit einer extrem hohen Beladung (12 Gew.‐%) einzelner Pt‐Atome wurden durch eine tensidgestützte Koordinationsstrategie synthetisiert. Die 2D‐Einzelatomkatalysatoren (SACs) weisen eine hervorragende photokatalytische Aktivität in der Wasserspaltung auf, mit einer hohen H2 ‐Produktionsrate von 11 320 μmol g −1 h −1 unter sichtbarem Licht (λ>420 nm).